Application research on fiber-optic current sensor in large pulse current measurement. (April 2020) - Ye, W; Dong, Z; Ren, R; Liu, J; Huang, K; Zhang, C
Abstract: Rogowski coil is usually used to measure pulse current in directed energy weapon experiments, which is lack of direct and low-frequency components in current measurement, and influenced by interferences like outside electromagnetic field and mechanical vibration. To acquire pulse current data with higher accuracy, a new kind fiber-optic current sensor is proposed to achieve large pulse current measurement, and working principle of the sensor is introduced in this paper. A fiber-optic current sensor is fabricated by cooperative agency, which has measuring range from 0 to 200kA and precision better than 1%. Comparison experiment between the fiber-optic current sensor and Rogowski coil made by PEM from England is tested. The experiment results show that main components of pulse current waves measured by two sensors are similar. Current wave measured by fiber-optic current sensor gets less noise signal than Rogowski coil, and has more details with small current. The fiber-optic current sensor could achieve direct and low-frequency component current measurement, but its max response frequency is 500 kHz. According to the research results, compared to Rogowski coil in pulse current measurement application, the new kind fiber-optic current sensor has better character in direct and low-frequency component current measurement, strong anti-interference ability, high sensitivity and ability to acquire current measurement data with higher accuracy. This sensor would satisfy measurement demands of large pulse current measurement in directed energy weapon better, if it gets better frequency response ability.